2018
DOI: 10.1242/jeb.183236
|View full text |Cite
|
Sign up to set email alerts
|

Potential trade-offs between biomineralization and immunity revealed by shell properties and gene expression profiles of two closely related Crassostrea species

Abstract: Species of the Ostreidae family are key ecosystem engineers and many of them - including and - are commercially important aquaculture species. Despite similarities in their morphology and ecology, these two species differ in their ability to defend against pathogens, potentially reflecting species-specific differential specialization of hemocytes on immune defense versus biomineralization. To test this hypothesis, we investigated the expression levels of immune- and biomineralization-related genes as well as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 72 publications
(109 reference statements)
1
24
0
Order By: Relevance
“…The calcium carbonate shell is predominantly laid down onto the periostracum by the epithelium of the outer mantle epithelium (Harper, 1997). We still have a poor knowledge of how calcium is mobilized within the animal to reach these specialized cells; however, in some species, such as Crassostrea, there is evidence to suggest that haemocytes may be involved, but this mechanism is not necessarily universal (Ivanina et al, 2018). Within outer mantle epithelial cells, experiments have demonstrated the active involvement of ion transporters in secreting calcium into the extra pallial space (Fig.…”
Section: Box 1 the Ecological And Socio-economic Benefits Of Calcifimentioning
confidence: 99%
“…The calcium carbonate shell is predominantly laid down onto the periostracum by the epithelium of the outer mantle epithelium (Harper, 1997). We still have a poor knowledge of how calcium is mobilized within the animal to reach these specialized cells; however, in some species, such as Crassostrea, there is evidence to suggest that haemocytes may be involved, but this mechanism is not necessarily universal (Ivanina et al, 2018). Within outer mantle epithelial cells, experiments have demonstrated the active involvement of ion transporters in secreting calcium into the extra pallial space (Fig.…”
Section: Box 1 the Ecological And Socio-economic Benefits Of Calcifimentioning
confidence: 99%
“…Though the mantle tissue of mollusk is primarily responsible for shell biomineralization, it has also been reported that oyster hemocytes can mediate shell biomineralization by binding calcium ion as well as forming CaCO 3 crystals [101103]. More recently, some studies also concluded that in addition to mineral transportation, hemocytes contribute to the secretion of the extracellular matrix required for shell biomineralization in bivalve [104, 105]. Therefore, the interaction between the epithelial cells of donor mantle and host hemocytes is very essential for the proper development of pearl sac and pearl [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been proposed that haemocytes, found in the open circulatory system of molluscs, may play an active role during shell formation by carrying amorphous calcium, calcium crystals or SMPs to the site of shell formation [ 11 13 ]. However, the involvement of haemocytes in mollusc biomineralization may be species-specific, as they were associated with immune processes in Crastostrea gigas , but with ion regulation and calcium transport in C. virginica [ 14 ]. While in vivo and in vitro experiments have identified SMPs as integral to shell production, the molecular players in other shell formation processes such as the uptake, mobilisation and storage of calcium and bicarbonate ions, are unclear [ 15 ].…”
Section: Backgroundkmentioning
confidence: 99%